A value-oriented psychological contract: Generational differences amidst a global pandemic - Deas, Alda; Coetzee, Melinde (Frontiers in Psychology, 2022)
The COVID-19 pandemic has changed the landscape of working conditions world-wide, fast tracking the reality of the digital-driven workplace. Concepts such as remote working, working-from-home and hybrid working models are now considered as the “new normal”. Employees are expected to advance, flourish and survive in this digitally connected landscape. Different age and generational groups may experience this new organisational landscape differently and may expect different organisational outcomes in exchange for their inputs. Accordingly, the study investigated differences regarding the value-oriented psychological contract expectations of employees from different generational groups. An ANOVA test for significant mean differences and a post hoc test for multiple comparisons were conducted on a sample of (N = 293) employees in the services industry in Southern Africa (85%) and other European countries (15%). The observed generational cohort differences regarding value-orientated psychological contract expectations for job characteristics and work-life balance could be utilised to develop interventions and strategies to promote retention of employees in the post-pandemic digital-orientated workplace.